Multifunctional Optoelectronic Synapse Based on Ferroelectric Van der Waals Heterostructure for Emulating the Entire Human Visual System. (23rd October 2021) - Guo, Feng; Song, Menglin; Wong, Man‐Chung; Ding, Ran; Io, Weng Fu; Pang, Sin‐Yi; Jie, Wenjing; Hao, Jianhua
Abstract: The development of optoelectronic synapses can provide an important breakthrough toward creating a sophisticated and adaptable artificial visual system analogous to that of humans. However, it remains a great challenge to implement the various functions of the biological visual neuromorphic system at the single device level. Intriguingly, 2D van der Waals (vdW) heterostructure may offer a platform to address the issue. Here, a novel multifunctional synaptic device based on ferroelectric α‐In2 Se3 /GaSe vdW heterojunction is proposed to emulate the entire biological visual system. Essential synaptic behaviors are observed in response to light and electrical stimuli; additionally, the retina‐like selectivity for light wavelengths and the achievement of Pavlov's dog experiment demonstrate the device's capacity for processing complex electrical and optical inputs. Beyond the optoelectronic synaptic behaviors, the device incorporates memory and logic functions analogous to those in the brain's visual cortex. The results of artificial neural network simulations show that the vdW heterojunction‐based device is completely capable of performing logic operations and recognizing images with a high degree of accuracy. The study indicates that versatile devices with a rationally designed construction have great potential for efficiently processing complex visual information and may simplify the design of artificial visual systems. Abstract : To emulate the entire human visual system at the single device level, a multifunctional optoelectronic synapse based on ferroelectric α‐In2 Se3 /GaSe vdW heterostructure is elaborately designed. Visual perception, logic functions, and memory are integrated into the device. The study shed light on creating a sophisticated artificial visual system analogous to that of humans and break the bottleneck of current image recognition technology.